If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -7 = 0 Reorder the terms: -7 + -1x = 0 Solving -7 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -1x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -1x = 0 + 7 -1x = 0 + 7 Combine like terms: 0 + 7 = 7 -1x = 7 Divide each side by '-1'. x = -7 Simplifying x = -7
| 5m-8m=36 | | 10-8x-10x+5= | | 11-x+61-x+x=180 | | 11-x+61-x=180 | | x+11-x+61-x=180 | | 4x=11x+21 | | (6y+8)-(2+5y)=7 | | -4x-(-4)=-35 | | a=34.2(17.5) | | x*2-12x+20=0 | | (4x+3)(x+1)=1 | | 6+-p=18 | | 14+x=-17 | | x+x+2+x+4=171 | | .75x+8=-20+.25x | | t^2+4z^2=0 | | 42+y=-25 | | -25=42+y | | x^4-7x^3-16x^2+172x=0 | | 3(2m-11)=3(m+10) | | x+3x=117 | | y=-4x+9 | | x+5(x+2)=46 | | x+x+12+2x=180 | | -3x+9=-9 | | 9x-12=3x+6x+12 | | -3x+22=y | | B^2-17b+72=0 | | w+w*2+6=24 | | 48x^2+98=0 | | Y=22-3x | | 5n=46 |